(untitled) (Acta Scientiarum. Education, 2020)
This article discusses the use of electronic books (E-Book), its potentiality and the analysis made for the construction of an E-book by the Mathematics teachers in a continuede ducation, developed with the purpose of working Digital Literacy with the involved ones. A survey instrument with open and closed questions was applied in order to seek the opinion of Math teachers about the use of E-books. This initial step was used to choose tools that can be performed during teacher education. One of the developed activities during the formation, consisted of face-to-face meetings and distance learning, another activity was the didactic materials construction through Digital Technologies, leading teachers to reflect on their practice using these tools, placing them as active subjects in the proposed actions, aspect concerning Digital Literacy. From the perspective of this research, we understand that it is necessary the development of a Digital Literacy by the teacher to later help his student develop his own Digital Literacy. E-book: Development and its potentiality